Beyond KRAS: Predictive factors of the efficacy of anti-EGFR monoclonal antibodies in the treatment of metastatic colorectal cancer - De Stefano, Alfonso (Baishideng Publishing Group Inc, 2014)
Systematic analysis of the epidermal growth factor receptor (EGFR) pathway revealed that biomarkers could be used to predict the response to and outcome of anti-EGFR therapies in patients affected by metastatic colorectal cancer. We have conducted a review on the most recent findings and advances on this topic. To this aim, we searched the PubMed database for articles devoted to predictive and prognostic biomarkers for patients administered cetuximab- and panitumumab-based therapies. Here we review the state of the art and the controversies about the molecular factors known to be predictors of the efficacy of anti-EGFR therapy, namely, KRAS, BRAF, NRAS, PI3KCA and PTEN, and we discuss their prognostic value in colorectal cancer patients.